Flexible ureteroscopy for upper tract urothelial carcinoma - Soria, Francesco; Gontero, Paolo; del Pilar Laguna Pes, Maria; de la Rosette, Jean J. M. C. H. (Springer Nature, 2022)
Flexible ureteroscopy (fURS) is an essential tool for the diagnosis, risk stratification, and treatment of upper tract urothelial carcinoma (UTUC). fURS should actually be performed in case of uncertainty, for kidney-sparing surgery (KSS), and even before radical surgery being able to provide important information for decision-making regarding perioperative systemic treatments. Flexible diagnostic URS is a stepwise procedure, starting with bladder cystoscopy and urine sampling for selective cytology and eventually ending with tumor ablation. Ureteral access sheaths can be used to allow for multiple biopsies, thereby diminishing the risk of inadequate tumor sampling. While the advent of digital scopes and that of enhanced technology imaging has dramatically improved the quality of the visualization of the upper urinary tract, a demonstration of their clinical utility over fiber-optic scopes is, to date, missing. Meanwhile, the experience of the surgeon and strict adherence to the guidelines recommendations remain the cornerstones of diagnostic fURS and KSS.
Keywords: Ablation; Biopsy; Digital; Flexible Ureteroscopy; Laser; NBI Image 1-S; UTUC